2017
DOI: 10.1039/c7ra05396g
|View full text |Cite
|
Sign up to set email alerts
|

Morphological analysis of cerium oxide stabilized nanoporous gold catalysts by soft X-ray ASAXS

Abstract: Soft X-ray SAXS and ASAXS reveal nanostructural properties and temperature induced morphological changes in catalyst materials. The stabilizing effect of cerium oxide deposits on the gold catalyst and the morphological properties of the cerium oxide were determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Whereas bulk gold is chemically inert, ceria nanostructures supported on Au(111) or on np-Au , exhibit remarkable catalytic activity, as discussed in the Introduction. Therefore, one can expect that ceria NPs play an important role in generating catalytically active sites in the CeO 2 /Au catalytic system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas bulk gold is chemically inert, ceria nanostructures supported on Au(111) or on np-Au , exhibit remarkable catalytic activity, as discussed in the Introduction. Therefore, one can expect that ceria NPs play an important role in generating catalytically active sites in the CeO 2 /Au catalytic system.…”
Section: Resultsmentioning
confidence: 99%
“…To reduce thermal and possible reaction-induced coarsening of np-Au, deposition of nanosized oxide particles (TiO 2 or CeO 2 ) offers an opportunity to drastically improve the thermal stability of this material and at the same time to increase its catalytic activity for oxidation reactions by opening new reaction pathways (e.g., Mars–van Krevelen mechanism discussed below). Furthermore, np-Au functionalized with reducible oxides becomes active for catalyzing further reactions, for which pristine np-Au is not catalytically active, for example, for the water–gas shift reaction , and steam reforming of methanol …”
Section: Introductionmentioning
confidence: 99%
“…Experimentally, it was demonstrated that the deposition of nanosized oxide particles (TiO 2 , Al 2 O 3 , or CeO 2 ) on np-Au improves its thermal stability significantly so that coarsening is prevented up to temperatures of 600 °C and above. , Besides, this modification leads to an increase in activity for aerobic oxidation reactions already catalyzed by pristine np-Au, such as CO oxidation. , Even more importantly, however, it was reported that the range of potential catalytic applications catalyzed by np-Au can be expanded by this step to reactions, such as NO reduction, the water–gas shift reaction, , and methanol steam reforming . It was suggested that in the case of reducible oxides, where the formation and healing of oxygen vacancies (denoted as O V in the following) are facile, the involvement of lattice oxygen opens new catalytic pathways increasing the activity or even enabling new types of reactions .…”
Section: Introductionmentioning
confidence: 99%
“…13 To reduce thermal and possible reaction-induced coarsening of npAu, deposition of nanosized oxide particles (TiO2 or CeO2) has been proven to be an opportunity to drastically improve the thermal stability of the material and at the same time to increase its catalytic activity. 25,[34][35][36][37] The TiO2 and CeO2 nano-particles supported on Au(111) and on np-Au have been found to be effective catalysts for the CO oxidation and NO reduction, 34,36,[38][39] water-gas shift reaction 34,36,[40][41][42] and steam reforming of methanol. 43 To the best of our knowledge, theoretical studies on gold catalysts functionlized with nanometallic-oxides (the inverse systems with respect to oxide-supported Au nanoparticles) are rare (in fact, we are aware of only one work 44 that dealt with O vacancy formation for such ceria/gold system) so that mechanistic details of oxidation reactions on such inverse catalysts still remain unclear.…”
Section: Introductionmentioning
confidence: 99%